Budidaya Ikan dalam Ember Berbasis Teknologi dan Manajemen untuk Pemberdayaan Masyarakat di Kabupaten Kendal - Adhisty Kartika Dewi; Maulida Putri Rahmawati; Eka Kurnia Patmasari (3026-1791, 2026)
Fish cultivation in buckets (budikdamber) is an appropriate technology that supports household food security and community income generation. This community service program aimed to improve the knowledge and skills of members of the Rowosari Subdistrict Youth Organization, Kendal Regency, in implementing Budikdamber through technology and business management. The program was conducted in collaboration with the Marine and Fisheries Office of Kendal Regency, the Kendal Regency Youth Organization, and the Rowosari Subdistrict Government. The activities consisted of preparation, implementation, monitoring, and evaluation through lectures, discussions, demonstrations, hands-on practice, and pre-test–post-test evaluation involving 33 participants. The results showed that participants' average understanding increased from 64.8% to 93.2%, while 96.97% of participants successfully assembled the Budikdamber system independently. The program effectively enhanced participants' knowledge and practical skills in applying appropriate aquaculture technology and basic business management for community empowerment.